Optimalisasi Peran Masjid Sebagai Pemberdaya Ekonomi Masyarakat (Studi Pada Masjid Agung Ponorogo, 2016) - Muhammad Abduh, Syamsuri & (Universitas Muhammadiyah Malang, 2017)
Since the time of the Prophet PBUH, mosques have a significant rules as a place of worship of Muslims, developing the economy of society, the place of wealth (Baitul Mal) which distribute zakat, alms, and spoils to the poor and the benefit of Muslims. Recently, the function of mosques not similar to the ancient time. In Ponorogo, there are approximately 481 mosques still not able to empower the local economy. Based on the research, the number of poor people in Ponorogo is still quite high, reached to 11.87% of the total population in East Java. The Tjokronegoro Mosque located in Ponorogo as the sample in this study because some of factors including steps strategy that has been done to empower the economy of the surrounding communities. The results of this study are expected to be a motivation and an example of economic empowerment through mosques, especially the East Java region. This research is qualitative descriptive, so the data collection method is using triangulation; documentation, interview and observation. Finally, this article found that the mosque Tjokronegoro Ponorogo Able to optimize their function in economic empowerment. Namely through three flagship programs: educational, humanitarian, and optimization of the distribution of zakah, infaq and sadaqah.